Biopsychosocial assessment in clinical health psychology - Andrasik, Frank, 1949-; Goodie, Jeffrey L.; Peterson, Alan L. (New York : The Guilford Press, 2015)
'Filling a key need, this practical volume provides state-of-the-art approaches and tools for evaluating both health-related behaviors and psychosocial aspects of medical illness. The book begins by presenting a comprehensive biopsychosocial assessment framework. Evidence-based strategies are described for assessing such key lifestyle factors as tobacco use, alcohol and other drugs, physical activity, and social support. Behavioral, cognitive, and emotional issues associated with a range of specific medical conditions--including cancer, cardiovascular disease, diabetes, chronic pain, and others--are addressed. Chapters on assessment of specific populations cover pediatric patients, older adults, ethnic/racial minority groups, organ transplant and bariatric surgery patients, and primary care'--Provided by publisher.
Part I. Overview -- ch. 1. Introduction to biopsychosocial assessment in clinical health psychology / Alan L. Peterson, Jeffrey L. Goodie, and Frank Andrasik -- ch. 2. Fundamentals of assessment in clinical health psychology / Cynthia D. Belar and William W. Deardorff -- ch. 3. Medication adherence / Howard Leventhal, ... [et al.] -- Part II. Assessment in health-risk behaviors -- ch. 4. Eating disorders / Susan Himes, Tovah Yanover, and J. Kevin Thompson -- ch. 5. Tobacco use / Alan L. Peterson, Antionette R. Brudige, and David Houghton -- ch. 6. Drug use and abuse / Deborah L. Haller, ... [et al.] -- ch. 7. Alcohol use / Tony Toneatto and Mekhala Gunaratne -- ch. 8. Social support / Merideth D. Smith and Amy Fiske -- ch. 9. Coping / Lauren M. Penwell-Waines, Kevin T. Larkin, and Jeffrey L. Goodie -- ch. 10. Physical activity / Patricia M. Dubbert, Todd A. Smitherman, and Jeanne Gabriele -- ch. 11. Quality of life / Jan Passchier and Jan Busschbach -- Part III. Assessment of clinical problems -- ch. 12. Cancer / Tammy A. Schuler, Thomas M. Atkinson, and Errol J. Philip -- ch. 13. Cardiovascular disease / Benson M. Hoffman, Ay Goetzinger, and James A. Blumenthal -- ch. 14. Chronic pain / Donald D. McGreary, ... [et al.] -- ch. 18. Gastrointestinal disorders / Branda B Toner and Iman Hussain -- ch. 19. Insomnia / Daniel J. Taylor, ... [et al.] -- Part IV. Assessment of special populations -- ch. 21. Cultural concerns / Luz Garcini, ... [et al.] -- ch.22. Organ transplant / Douglas P. Gibson, ... [et al.] -- ch. 23. Bariatric surgery / Mary Ellen Olbrisch, Melanie K. Bean, and Karen E. Stewart -- ch. 24. Pediatrics / Lisa M. Buckloh and Lisa M. Schilling -- ch. 25. Older adults / Christine E. Gould, Merideth D. Smith, and Barry A. Edelstein -- ch. 26. Primary care / Christopher L. Hunter.
Machine generated contents note: I. Overview 1. Introduction to Biopsychosocial Assessment in Clinical Health Psychology, Alan L. Peterson, Jeffrey L. Goodie, & Frank Andrasik 2. Fundamentals of Assessment in Clinical Health Psychology, Cynthia D. Belar, & William W. Deardorff 3. Medication Adherence, Howard Leventhal, Danielle E. McCarthy, Elaine A. Leventhal, & Krysten Williams BoldII. Assessment of Health-Risk Behaviors 4. Eating Behaviors/Obesity, Susan Himes, Tovah Yanover, & J. Kevin Thompson 5. Tobacco Use, Alan L. Peterson, Antoinette R. Brundige, & David Houghton 6. Drug Use and Abuse, Deborah L. Haller, Michelle C. Acosta, Howard Newville, & Abigail Herron 7. Alcohol Use, Tony Toneatto & Mekhala Gunaratne 8. Social Support, Merideth D. Smith & Amy Fiske 9. Coping, Lauren M. Penwell-Waines, Kevin T. Larkin, & Jeffrey L. Goodie 10. Physical Activity, Patricia M. Dubbert, Todd A. Smitherman, & Jeanne Gabriele 11. Quality of Life, Jan Passchier & Jan BusschbachIII. Assessment of Clinical Problems 12. Cancer, Tammy A. Schuler, Thomas M. Atkinson, & Errol J. Philip 13. Cardiovascular Disease, Benson Hoffman, Amy Goetzinger, & James A. Blumenthal 14. Chronic Pain, Donald D. McGeary, Robert J. Gatchel, Cindy A. McGeary, & Monica Escamilla 15. Headaches, Dawn C. Buse, Frank Andrasik, & C. Mark Sollars 16. Dental Pain, Alan G. Glaros 17. Diabetes, Linda Gonder-Frederick, Laura K. Campbell, & Jaclyn A. Shepard 18. Gastrointestinal Disorders, Brenda B. Toner & Iman Hussain19. Sleep Disorders, Daniel J. Taylor, Christina S. McCrae, Kenneth L. Lichstein, & Adam D. Bramoweth 20. HIV/AIDS, Anne-Lise C. Smith, Dean G. Cruess, & Seth C. Kalichman IV. Assessment of Special Populations 21. Cultural Concerns, Luz Garcini, Kate Murray, Jessica Barnack-Tavlaris, & Elizabeth A. Klonoff 22. Organ Transplant, Douglas P. Gibson, Kristin Kuntz, Solam Huey, & Mary Ellen Olbrisch 23. Bariatric Surgery, Mary Ellen Olbrisch, Melanie K. Bean, & Karen E. Stewart 24. Pediatrics, Lisa M. Buckloh & Lisa M. Schilling 25. Older Adults, Christine E. Gould, Merideth D. Smith, & Barry A. Edelstein 26. Primary Care, Christopher L. Hunter Author Index Subject Index.
Includes bibliographical references and indexes.
Keywords: Psychology, Clinical -- methods; Behavioral Medicine -- methods; Psychology, Medical -- methods